Transformation of the relations of power between evaluation and education (2016)
Relationship between education and evaluation has been marked by relations of power. Society, State and educational institutions have validated those relations by deviating them from the true principles of educational evaluation. In this study it was possible to demonstrate and understand those relations exist, allowing to identify teacher trainees’ concepts on evaluation, and to change them by transforming the evaluation practices through the reflection on action. This study, conducted with teacher trainees in Bachelor of Humanities and Languages at a university in Bogota, follows action research as its methodology, and it is framed in the qualitative paradigm.